Playing Origami Enhance The Creativity Of School Aged Children - Yuni Sufyanti Arief; Dhianita Binarwati; Ratri Ismiwiranti (Universitas Airlangga, 2008)
Introduction: Critical period for creativity development happened at school aged. Playing Origami is a stimulation that can be done to develop child’s creativity optimally. The aimed of this study was to analyze the effect of playing origami toward creativity development at school age in 4th grade elementary school Krian, Sidoarjo.Methods: This study was used a pre experimental and purposive sampling design. The populations were children who age in the sixth until seventh age in 4th grade elementary school Krian, Sidoarjo. There were 41 respondents for this research who met the inclusion criteria. The independent variable was the playing origami while the dependent variable was creativity development of school age. Data were collected by using questionnaire and Figural Creativity test to know the creativity level before and after intervention, and then analyzed by using Wilcoxon Signed Rank Test with significance level of a£0.05.Results: The result showed that there was an effect of play origami toward the creativity development of school age with significant level (p=0.000).Conclution: It can be concluded that playing origami can develop the creativity of school aged children. Every child should be facilitated by provide a chance, supportt and activity that can improve their creativity development that can be useful for them and other people. Further study was recommended to analyze the effect of playing origami on decreasing stress hospitalization.